2018
DOI: 10.5424/sjar/2018161-11484
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vapour pressure deficit patterns during cucumber cultivation in a traditional high PE tunnel greenhouse and a tunnel greenhouse equipped with a heat accumulator

Abstract: Plant productivity in protected cultivation is highly influenced by air temperature and humidity. The conditions relating to the moisture content of the air in protected plant cultivation are preferably defined by vapour pressure deficit (VPD), which describes the difference between the maximal and actual water vapour pressure (kPa). VPD is widely used as the parameter describing the climate conditions favourable for the development of fungal diseases and for highlighting conditions unfavourable for plant deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In general it can be seen that the average values for the hours of the day are very close to the recommended minimum value of 0.4 kPa and are far below the optimum value of 0.85 kPa necessary to ensure good biological and physiological functioning of the plants and to limit the development of pests and diseases as much as possible. On the other hand, for the night period the value obtained is inadequate since values lower than 0.2 kPa facilitate the development of fungal diseases (Konopacki et al, 2018).…”
Section: Temperature Relative Humidity and Vpdmentioning
confidence: 95%
“…In general it can be seen that the average values for the hours of the day are very close to the recommended minimum value of 0.4 kPa and are far below the optimum value of 0.85 kPa necessary to ensure good biological and physiological functioning of the plants and to limit the development of pests and diseases as much as possible. On the other hand, for the night period the value obtained is inadequate since values lower than 0.2 kPa facilitate the development of fungal diseases (Konopacki et al, 2018).…”
Section: Temperature Relative Humidity and Vpdmentioning
confidence: 95%
“…Therefore, we proceed to the next phase of geostatistical analysis which is to construct the omnidirectional semivariogram. The VPD levels inside the greenhouse are not the most suitable for rose production, since it is recommended that the values of this variable are located in a range of 0.4 and 1.2 kPa, this in order to limit as much as possible negative effects on the photosynthetic rate of the plant and the generation of an environment favorable to the emergence and survival of fungal diseases (Konopacki et al, 2018). Low VPD values also affect plant nutrition by causing deficiencies influenced by poor movement of sap flow (Shamshiri et al, 2018).…”
Section: Vapour Pressure Deficit (Vpd)mentioning
confidence: 99%
“…The implementation of a greenhouse additionally seeks to provide crop protection from biotic and abiotic factors, which promotes an increase in the quantity and quality of the final product harvested compared to open field production . For rose production under greenhouse the following microclimate conditions are recommended as being optimal for production, the temperature value should be between 18 and 25 °C for the day period (Kinfe et al, 2014) and for the night period between 14 and 18 °C (Reid, 2008), on the other hand it is appropriate that the relative humidity conditions are above 70% during the day and maximum 85% at night (Torre and Fjeld, 2001), likewise the value of the vapour pressure deficit should be between 0.4 and 1.2 kPa for the day and between 0.2 and 0.4 kPa for the night (Konopacki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the eastern part of the greenhouse, concurrent with the increase in temperature, there could be seen an increase in humidity compared to the western part and the center of the greenhouse, which reduced the VPD in this part. Between the opening of the side wall vents at 8:30 until about noon when the air temperature inside the greenhouse started increasing, the intrusion of cold weather from the western ventilation vent, caused a decrease in the humidity weather maintenance capacity by reducing the temperature [ 35 ]; thus, the value of VPD was lower in the eastern part of the greenhouse ( Figure 8 e and Figure 9 e). A review of the VPD horizontal distribution at 6:00 showed that the western section of the greenhouse had lower VPD values than the eastern part ( Figure 9 e).…”
Section: Resultsmentioning
confidence: 99%